2019
DOI: 10.3389/fpsyg.2019.01981
|View full text |Cite
|
Sign up to set email alerts
|

Masked Speech Recognition in School-Age Children

Abstract: Children who are typically developing often struggle to hear and understand speech in the presence of competing background sounds, particularly when the background sounds are also speech. For example, in many cases, young school-age children require an additional 5- to 10-dB signal-to-noise ratio relative to adults to achieve the same word or sentence recognition performance in the presence of two streams of competing speech. Moreover, adult-like performance is not observed until adolescence. Despite ample con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 77 publications
3
36
0
1
Order By: Relevance
“…For example, in speech intelligibility tasks, when the interfering sound is (non-speech) noise, children achieve adult-like performance by the age of 9-10 years. However, when the interfering sound is speech, there is a prolonged developmental trajectory, with adult-like performance not reached until adolescence [15]. Although older adults generally have greater difficulty in understanding masked speech than younger adults, competing talkers seem to be particularly detrimental for older listeners as well [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in speech intelligibility tasks, when the interfering sound is (non-speech) noise, children achieve adult-like performance by the age of 9-10 years. However, when the interfering sound is speech, there is a prolonged developmental trajectory, with adult-like performance not reached until adolescence [15]. Although older adults generally have greater difficulty in understanding masked speech than younger adults, competing talkers seem to be particularly detrimental for older listeners as well [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One potential mechanism that explains the link between cognitive and linguistic skills and listening in noise and reverberation is related to children's increased susceptibility to informational masking (Brungart et al, 2001; see Leibold and Buss, 2019 for a review). Reverberation is a particularly challenging masking signal because the reverberant signal can cause energetic masking, where the energy of the reverberant signal overlaps with the target signal in the auditory system.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the stimuli used during the task, and similarity between targets and interferers play an important role in determining the effect sizes and differences between children and adults (see Litovsky et al, 2017, for a review). A recent review suggests that there are numerous factors, both peripheral and central, that may impact age-related changes in the ability to identify and understand target speech in noise (Leibold & Buss, 2019). For example, Buss et al (2016) showed that release from masking in children with NH as young as 5 years of age is impacted by the fact that children use context less than adults, rendering top-down repair or restoration of target speech less beneficial.…”
Section: Introductionmentioning
confidence: 99%